2015
DOI: 10.1097/ta.0000000000000833
|View full text |Cite
|
Sign up to set email alerts
|

Impact of common crystalloid solutions on resuscitation markers following Class I hemorrhage

Abstract: Therapeutic study, level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…There is in fact some evidence that saline may be harmful. In the adult, in addition to vasodilatation, saline infusion leads to acidosis . In preterm piglets, saline infusion of 10–30 mL/kg does not improve mean arterial pressure and is associated with increased acidosis and a more negative arterial base excess (Figure ).…”
Section: Blood Volume In the Preterm Infantmentioning
confidence: 99%
“…There is in fact some evidence that saline may be harmful. In the adult, in addition to vasodilatation, saline infusion leads to acidosis . In preterm piglets, saline infusion of 10–30 mL/kg does not improve mean arterial pressure and is associated with increased acidosis and a more negative arterial base excess (Figure ).…”
Section: Blood Volume In the Preterm Infantmentioning
confidence: 99%
“…In particular, the acidosis associated with unbalanced crystalloids might further contribute to the lethal triad of coagulopathy during major bleeding. 116 In the prehospital treatment of traumatic hypovolaemic shock, two small studies showed that hypertonic fluid resuscitation does not improve outcome compared to other crystalloids, and can even worsen the coagulation status. 117,118 In a propensitymatched analysis of women receiving HES 130/0.4 or balanced crystalloids, no association was observed between HES use and perioperative blood loss during caesarean delivery.…”
Section: Acute Major Bleedingmentioning
confidence: 99%
“…Results on lactate and base deficit from this work have been previously reported, but this study examined the topic of hemodilution using the hemoglobin findings, which were not included in the previous report. 11 The analysis of hemoglobin and effect of hemodilution were planned a priori, and the intended primary outcome randomization was designed to investigate, but was too large to include in a single publication. The study design and procedure were described in detail in the previous work, but in brief, the authors partnered with the Carolinas Trauma Network Research Center of Excellence 13 and the Community Blood Centers of the Carolinas (CBCC) 14 to conduct the randomized control trial in parallel with blood drives at major hospitals in the Carolinas HealthCare System (CHS) (Charlotte, NC).…”
Section: Donor Population and Study Designmentioning
confidence: 99%
“…To evaluate these questions, we performed a secondary analysis of hemoglobin values in our previously published randomized control trial using voluntary blood donors and subsequent resuscitation with normal saline (NS), lactated Ringer's (LR), or no resuscitation (control). 11…”
mentioning
confidence: 99%